1163 Genome-wide Association Study Reveals 55 Loci Associated with Gallstone Disease. (12th October 2021) - Fairfield, C; Spiliopoulou, A; Wigmore, S; Harrison, E
Abstract: Aim: Gallstones have a prevalence of 20-40% in European populations and cause significant morbidity. Gallstones form from cholesterol and calcium bilirubinate and knowledge of genetic determinants remains incomplete. A genome-wide association study (GWAS) was performed to identify determinants of gallstones. Method: A GWAS of 16, 356, 211 single nucleotide polymorphisms (SNPs) for 28, 627 cases and 348, 373 controls of European ancestry in the UK Biobank was undertaken. A logistic regression with additive allelic dosage was performed (significance: P < 5*10 -8 ). Functional annotation and linkage disequilibrium clumping were performed to reveal distinct loci. Lead SNPs were investigated by linear regression for association with plasma lipids, liver enzymes and blood count markers. Results: 55 lithogenic loci were identified of which 27 are novel. Functional annotation revealed genes involved in metabolism of cholesterol, glucose, bile acids and bilirubin with corresponding changes in serum biomarkers caused by those lithogenic alleles. Several novel variants did not alter cholesterol or other biomarkers. Lithogenic variants within genes controlling intra- and paracellular transport may govern biliary composition (PCDHB4, NUP153, CLDN7) and promote lithogenic bile. Variants within genes which may influence gallbladder motility (ANO1, TMEM147) and cholangiocyte ciliogenesis (TBC1D32, ADAMTS20, DYNC2LI1, HNF1B) may promote gallstone formation through reduced biliary flow. Conclusions: We identified 27 novel associations with gallstones. Impact of lithogenic alleles on serum biomarkers was highly variable demonstrating that gallstone formation is partially driven by pathways which do not influence cholesterol, glucose or bilirubin metabolism. Variants within genes that may influence biliary composition, bile flow and gallbladder motility represent new targets for research into gallstones.